ANALISIS PENGGUNAAN ALAT KONTRASEPSI PADA PASANGAN SUAMI ISTRI DALAM PELAKSANAAN PROGRAM KB DI WILAYAH KERJA PUSKESMAS MEDAN AMPLAS - Hotmarina Septiani Nainggolan, Ivena; Susilawati (Lafadz Jaya Publisher, 2022)
Family Planning (KB) is an attempt to measure the number and distance of children desired. To be able to achieve this, several ways or alternatives are made to prevent or delay pregnancy. For this reason, a family planning program was held by recording the use of contraceptives in the area. A contraceptive device is a device, medication, or surgical procedure that serves to delay or stop having children. There are many types of contraceptives available, from birth control pills, birth control injections, condoms, to sterilization procedures such as tubectomy for women, or vasectomy for men. The purpose of this study was to determine the use of contraceptives in carrying out family planning programs in the working area of Medan Amplas Public Health Center. The research method used is quantitative method using a cross sectional study approach taken from tertiary data instruments with univariate, bivariate and multivariate data analysis. The result of this study is that there are 100 respondents who carry out family planning programs using contraception. Around 60.5% of the people in the working area of the Medan Amplas Public Health Center do not carry out the family planning program and about 39.5% of the people use contraceptives as their family family planning program.